Th17/Regulatory T Cell Imbalance in Sepsis Patients with Multiple Organ Dysfunction Syndrome: Attenuated by High-volume Hemofiltration. Issue 11 (November 2017) - Guo, Jiguang; Tao, Wu; Tang, Dan; Zhang, Jianbin
Background: We assessed the Th17 (T-helper cell)/Treg (Regulatory T cell) imbalance in sepsis patients with multiple organ dysfunction syndrome (MODS) and the clinical benefits of continuous high-volume hemofiltration (HVHF). Methods: 48 sepsis patients, including 22 patients with MODS (MODS group, n = 22) and 26 without (non-MODS group, n = 26), and 20 healthy volunteer controls were enrolled. The patients in MODS group were randomly divided into the continuous blood purification (CBP) group (n = 11) receiving conventional comprehensive treatment plus high-volume hemofiltration and the non-CBP group (n = 11) receiving conventional comprehensive treatment only. At day 28, all 48 patients were divided into the survival group (n = 36) and the non-survival group (n = 12). Venous blood samples, collected at 0, 6, 12 and 24 hours during hemofiltration (or equivalent times in the non-CBP group), were assessed by flow cytometry to detect the Th17 and Treg cells in peripheral blood. Serum cytokines (such as IL-6, IL-17, IL-23, IL-10 and TGF-β1) were detected by enzyme-linked immune sorbent assay (ELISA). Results: Th17%, Treg%, Th17/Treg, IL-6, IL-17, IL-23, IL-10 and TGF-β1 were significantly higher in MODS and non-MODS group than in the health control (p<0.05), while Th17%, Treg%, Th17/Treg and measured cytokines were significantly higher in the MODS group compared to the non-MODS group (p<0.05). After HVHF treatment, Th17%, Treg%, Th17/Treg, IL-6, IL-17, and IL-10 were significantly reduced (p<0.05), while there were no significant changes in the non-CBP group (p>0.05). In addition, APACHE II and SOFA scores decreased markedly after HVHF treatment. Baseline Th17%, Treg%, Th17/Treg, IL-6, IL-17, IL-23, IL-10 and TGF-β1 were significantly higher in the non-survival group compared to the survival group. Both Th17% and Th17/Treg were positivity correlated with concentration of IL-6 and APACHE II score (p<0.01). Conclusions: The level of Th17/Treg imbalance in sepsis is related to the occurrence and prognosis of MODS. High-volume hemofiltration can attenuate the Th17/Treg imbalance in sepsis patients, possibly by removing inflammatory mediators.